Analytical and Modelling Study on the Spatial Stress Distribution and Failure Process of Disc Specimen in the Brazilian Splitting Test. (22nd December 2021) - Zhang, Wei; Guo, Wei-yao; Wang, Zhi-qi
Abstract : To correctly obtain the spatial stress distribution and failure process of disc specimen in the Brazilian splitting test, an analytical solution of three-dimensional stress is deduced. Then, the effects of height-diameter ratio and clamp radian on the spatial stress distribution and failure process are analyzed and studied combined with numerical modelling. At last, the influence of spatial effect on the tensile strength of disc specimen is discussed. The results show that the cracks firstly generate at the two ends of the specimen in the axial direction and then extend due to the nonuniform distribution of tensile stress. The macrocracks coalescence does not mean the capacity loss of radial bearing. The maximum radial bearing capacity of the disc specimen decreases with the increase of height-diameter ratio due to the spatial effect. The tensile strength obtained by the two-dimensional calculation formula is significantly smaller. Therefore, when the commonly-used height-diameter ratio of 0.5 is used in the Brazilian splitting test, a correction factor k = 1.15 − 1.25 is suggested.